The Accumulation of Standards for Treatment Decisions in Social Work (1847-2018) - Filip Wollter (Social Work and Society)
The choice of treatment in social work is characterized as discretionary since it should be adapted to the individual context and there are diverse and debatable ways to improve living conditions in question. Existing research has found that streel-level bureaucrats, such as social caseworkers, base their discretionary decisions on multiple standards, or"actions prescriptions". Taking this pluralism into account, this article explores and contextualizes the development of standards for discretionary treatment decisions, using the case of Swedish public social casework (1847-2018). The aim is to expose and compare various approaches and types of discretion, their origins, and the conditions of their coexistence. The study has two main empirical findings. First, the development of new standards for the exercise of discretion is justified by the fact that the new standard is a better knowledge base for treatment decisions. The driving motor of these changes is mainly advocacy by civil society organizations. Second, as the advocacy of new standards was successful, in several cases, it has resulted in the accumulation, or sedimentation, of standards. The consequence is that an increasing number of discretionary actors balance different action descriptions and negotiate for discretionary power.